2018
DOI: 10.1177/0192636518782427
|View full text |Cite
|
Sign up to set email alerts
|

Policies and Practices Supporting LGBTQ Students in Indiana’s Middle Schools

Abstract: Principals should lead for social justice, particularly in support of marginalized and vulnerable students like lesbian, gay, bisexual, transgender, and questioning (LGBTQ) adolescents. This quantitative survey-based study collected data from 116 middle grade principals in Indiana to examine the implementation of antibullying policies and best practices supporting LGBTQ students. Findings suggest that utilization of research-based policies and practices may provide protection and support to LGBTQ students from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The significance of this research is the implication that using gender pronouns during written communication can foster a better culture of DEI principles, and help organizations redesign the way they develop websites, emails, questionnaires, employee applications, and public relations with personnel and clients. Organizational practices should signal identity-safety cues and values supporting LGBTQIA+ individuals with the explicit acknowledgement and inclusion of one’s gender pronouns in organizational materials ( Boyland et al, 2018 ; Gay, Lesbian and Straight Education Network [GLSEN], 2020 ; Johnson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this research is the implication that using gender pronouns during written communication can foster a better culture of DEI principles, and help organizations redesign the way they develop websites, emails, questionnaires, employee applications, and public relations with personnel and clients. Organizational practices should signal identity-safety cues and values supporting LGBTQIA+ individuals with the explicit acknowledgement and inclusion of one’s gender pronouns in organizational materials ( Boyland et al, 2018 ; Gay, Lesbian and Straight Education Network [GLSEN], 2020 ; Johnson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Schools with higher reported implementation of inclusive and anti-discriminatory policies had lower levels of discrimination against LGBTQ youth [12], fostering a safer school space. Effective bills such as Bill 13 (i.e., Accepting Schools Act, Ontario, Canada) allowed LGBTQ youth to create a space to transform their lives and offer opportunities of activism [52].…”
Section: The Implementation Of Inclusive and Anti-discriminatory Poli...mentioning
confidence: 99%
“…The identification of an adult ally predicted a decrease in fear-based truancy [72,99,100]. Principals agreed that there is a need to increase efforts to reduce discrimination towards LGBTQ youth by setting a safe and positive climate in schools [12]. An avenue that was effective in creating an inclusive and affirmative environment and reduce health risks among LGBTQ youth are school-based health centers [125].…”
Section: High Level Of Within-school Adult Support Reduces Negative O...mentioning
confidence: 99%
“…Russell, Kosciw, Horn, and Saewyc (2010) found LGBTQ students' feelings of safety and well-being increased when faculty members were trained on intervention techniques for bullying or harassment. These and other research-based practices for supporting LGBTQ students have been identified and compiled (Boyland, Kirkeby, & Boyland, 2018); thus, principal candidates need to learn these best practices during their preparation programs.…”
Section: Implications For Higher Education Principal Preparation Progmentioning
confidence: 99%